From needs' analysis to Community of Practice about Teaching and Learning in HE: the University of Genoa's experience - Antonella Lotti (Firenze University Press, 2018)
Some teachers from eight Italian universities have become members of the Italian Association for the Development of Teaching and Learning in Higher Education (ASDU). ASDU promoted a survey based on a questionnaire developed by the University of Padua to identify teachers' beliefs, best practices and training needs. The questionnaire has been administered at the University of Genoa. Results show that faculty members would appreciate both formal and informal training activities. This paper focuses on the request and building up of one of the first experiences of Communities of Practice devoted to academic teaching. Dall'analisi dei fabbisogni formativi alle Comunità di Pratica sulla didattica universitaria: l'esperienza dell'Università di Genova Alcuni docenti di otto università italiane hanno aderito alla Associazione Italiana per lo Sviluppo della Didattica, dell'apprendimento e dell'insegnamento in Università (ASDU). L'ASDU ha promosso l'utilizzo di un questionario creato dall'Università di Padova per effettuare un'indagine su credenze, buone pratiche e bisogni formativi dei docenti universitari. Il questionario è stato somministrato presso l'Università di Genova. Dai risultati emerge che i docenti desiderano avere occasioni di formazione informale e formale. Questo lavoro si sofferma sulla richiesta e avvio delle prime Comunità di Pratica dedicate alla didattica universitaria.